Pierre, feuille, ciseaux - Stéphanie Wyler (Cahiers Mondes Anciens)
Representing a view on the nature requires drawing a frame to such a referent that is obviously larger than the borders of the image. This paper deals with a corpus of six paintings and mosaics, conceived as parts of a broader decoration on walls and floors. It shows the way “landscapes” are cut, framed, how they are extended beyond their borders strongly depicted as pinakes or emblemas, or how they melt into the background. Such layouts vary which natural elements are selected, their scale, their bounds, the points of view on them. They throw light on Roman gaze on nature, that reveals a religious, erudite or erotic potential from a context to another.